Spatial contextual effects in primary visual cortex limit feature representation under crowding - Christopher A. Henry (Nature Portfolio, 2020)
Visual crowding can strongly limit perceptual discriminability, yet its neural basis remains unclear. Here, the authors show that perceptual crowding is similar in monkeys and humans, and that feature encoding in neuronal populations in primary visual cortex is limited for displays inducing crowding.